Bar el Chino - Burak, Daniel; Levit, Mario Ezequiel; Lion, Mario; Latorre, Jimena; Dioguardi, Pasta; Sanchez, Nestor; Santa Ana, Lucas; Larrese, Ernesto (Vocacion S.R.L., 2003)
Two filmmakers fall in love with each other and with Bar "El Chino", where tango is sung. Captivated, they work together on a documentary project about the Bar in an effort to capture the magic and essence of the place.